Predictors of Reading Fluency in Second and Third Grade Students: Results from Bosnia and Herzegovina - Haris Memisevic; Inga Biscevic; Arnela Pasalic; Daniel Malec (Studia Psychologica, 2019)
Learning to read is one of the most important academic accomplishments in the early grades of elementary school. Knowing what factors contribute to reading ability would improve instructional practices. The goal of the present study was to examine the effects of semantic fluency, phonological fluency, rapid naming, inhibitory control, selective attention, and visual motor integration on reading fluency in 140 second and third grade students. The results of this study indicated that significant predictors of reading fluency were: selective attention, semantic fluency, inhibitory control, and rapid naming. However, the association between predictor variables and reading fluency was moderated by the students’ grade. The article concludes with some suggestions on how to improve reading fluency in elementary school children, given that all predictors are susceptible to instruction.